Empowering Students in Plantation-Based Entrepreneurship Education at Senior High School 1 Payaraman - Neta Dian Lestari; Reva Maria Valianti; Nur Ahyani; Anisah Anisah; Aan Nugraha; Violita Fadhilah (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: This Community Service project addressed the underutilization of the school garden at SMAN 1 Payaraman, which had been limited to the production of raw agricultural materials. The core problems identified were the critical lack of added value in products and the students' limited knowledge of essential entrepreneurial competencies, including post-harvest handling, product processing, effective marketing, and digital financial management.Aims: The program aimed to significantly enhance the entrepreneurial skills of SMAN 1 Payaraman students by training them to process their plantation products into high-economic-value goods. The comprehensive scope included the transfer of practical skills in product processing, efficient production management, professional packaging techniques, and digital marketing strategies.Method: The program was implemented through five stages: socialization, product training, packaging, production management, and marketing implementation. Essential equipment (oven/dehydrator, grater) was provided to support sustained, long-term production.Result: The program had a significant positive impact, as evidenced by the substantial improvement in students' practical skills and high participant satisfaction, particularly in marketing training. In addition, the program achieved the successful acquisition of Intellectual Property Rights (IPR) for the developed products. Overall, the program successfully transformed the perspective of the school community, enabling them to produce high-economic-value goods from raw materials.Conclusion: The program directly empowered students of SMA Negeri 1 Payaraman with practical entrepreneurial skill based on school plantation product. The program also contributed to to enhance the overall school entrepreneurial ecosystem, including teachers and school management, through increased revenue, market expansion, and the adoption of a digital financial system to ensure the program's long-term sustainability.